Building resilient infrastructure for the future background paper for the G20 climate sustainability working group. (Metro Manila, Philippines Asian Development Bank, 2019)
It was prepared to provide inputs for discussions at the Group of Twenty (G20) Climate Sustainability Working Group meeting in Tokyo, Japan, in February 2019. It provides insights on the experience of and lessons learned by the Asian Development Bank on resilient infrastructure and highlights opportunities for future partnerships and synergies with partners in the development and finance communities regionally and internationally. It also explores new financing modalities for building resilient infrastructure.
Keywords: Climatic change; Climatic changes -- Government policy; Electronic books